Angiogenic factors in relation to embryo implantation - Bagheri, Azadeh; Chianeh, Yousef Rezaei; Kumar, Pratap; Rao, Pragna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Disturbances in uterine blood supply are associated with higher perinatal morbidity and mortality caused by preterm delivery, preeclampsia or intrauterine growth restriction. Adaptation of the uterine vasculature to the rising needs of the fetus occurs through both vasodilation and development of new vessels. Angiogenesis is the process of neovascularization from pre-existing blood vessels in response to hypoxic condition of tissues. The endometrium, decidua and placenta are rich sources of angiogenic growth factors. In general, the angiogenic process is initiated by growth factors such as VEGF, placental growth factor (PlGF) or bFGF. Through a complex signal transduction machinery mediated by respective receptor-tyrosine kinases, an increase in the permeability of the maternal vessels is achieved to permit growth and invasion of endothelial cells. Their chemotactic migration, formation of a vessel lumen, and functional maturation of new capillaries complete the angiogenic process that involves the expression of specific adhesion receptors and extracellular matrix-degrading proteases. During vasculogenesis, endothelial progenitor cells–angioblasts–form a primitive vascular network. This process occurs mainly during fetal development, although recruitment of angioblasts from bone marrow and peripheral blood in response to ischemic insult have been described in adults. In this review article we have described a recent complication related to angiogenic involvement in embryo implantation.